2022
DOI: 10.3389/fvets.2022.998956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guanidine acetic acid on meat quality, muscle amino acids, and fatty acids in Tibetan pigs

Abstract: This study investigated the effects of guanidine acetic acid (GAA) supplementation on growth performance, carcass traits, and meat quality in Tibetan pigs. A total of 18 male Tibetan pigs (21.35 ± 0.99 kg) were randomly assigned to the control (basal diet) and GAA (basal diet + 800 mg/kg GAA) groups for 125 days. Growth performance, carcass traits, and meat quality in pigs, and the chemical composition of Longissimus thoracis (LT) were not altered by GAA. In LT, compared to the control group, dietary GAA incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A reduction in MDA levels has been associated with a potential decrease in oxidative damage ( Li et al, 2022 ), suggesting that dietary GAA at a level of 0.6 g/kg is effective in mitigating oxidative stress. Previous studies have also highlighted the potential antioxidant effects of supplemental GAA in low to moderate quantities ( Amiri et al, 2019 ; Cui et al, 2022 ). In contrast, Ostojic (2015) demonstrated that an excess of GAA in the body or an abnormal metabolic process involving this compound can result in a pro-oxidant effect, which leads to the generation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in MDA levels has been associated with a potential decrease in oxidative damage ( Li et al, 2022 ), suggesting that dietary GAA at a level of 0.6 g/kg is effective in mitigating oxidative stress. Previous studies have also highlighted the potential antioxidant effects of supplemental GAA in low to moderate quantities ( Amiri et al, 2019 ; Cui et al, 2022 ). In contrast, Ostojic (2015) demonstrated that an excess of GAA in the body or an abnormal metabolic process involving this compound can result in a pro-oxidant effect, which leads to the generation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the ratio of PUFA to SFA, which serves as a significant marker of lipid quality ( Sinanoglou et al, 2011 ), demonstrated a significant increase following the inclusion of GAA supplementation in the dietary regimen. In a recent investigation conducted by Cui et al (2022) , it was found that GAA supplementation led to an increase in the concentrations of linolenic acid (C18:3n-3), arachidonic acid, and total PUFA in the Longissimus thoracis muscle in Tibetan pigs. Our findings suggest that the observed increase in the levels of C18:2n-6 in egg yolk can potentially be attributed to the enhanced efficacy of GAA in facilitating the transportation and deposition of this fatty acid within the yolk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle contents of dry matter, crude protein, ether extract, inosinic acid, and fatty acids were determined according to Cui et al's [12,14] and Chinese standards and general protocols using an ALPHA 2-4 LSC freeze-dryer (Martin Christ GmbH, Osterode am Harz, Germany), an 8400 nitrogen analyzer (FOSS, Hillerød, Denmark), an ether extract analyzer (2055 SOXTEC, FOSS, Hillerød, Denmark), an LC-20AD high-performance liquid chromatograph (Shimazu, Kyoto, Japan), and a 6890 gas chromatograph (Agilent, Santa Clara, CA, USA), respectively.…”
Section: Chemical Composition Determinationmentioning
confidence: 99%